2015
DOI: 10.1186/s13148-015-0149-2
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation status and expression of PPAR-γ gene are associated with prognosis of acute-on-chronic hepatitis B liver failure

Abstract: BackgroundPeroxisome proliferator-activated receptor gamma (PPAR-γ) has been demonstrated to be involved in anti-inflammatory reactions, but its role in acute-on-chronic hepatitis B liver failure (ACHBLF) is unclear. Therefore, DNA methylation patterns and expression level of PPAR-γ gene were detected in peripheral blood mononuclear cells (PBMCs) from 81 patients with ACHBLF, 50 patients with chronic hepatitis B (CHB), and 30 healthy controls, and the possible role of PPAR-γ in ACHBLF was analyzed.ResultsWe fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…TNF-α is a cytokine involved in systemic inflammation. In fulminant liver failure, the serum level of TNF-α was significantly increased correlated with serious complications, such as infection and HE (de la Mata et al 1990;Zhao et al 2015). In the process of necroptosis, MLKL was phosphorylated and insert into the plasma membranes and organelles, which resulted in the expulsion of cellular contents into the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a cytokine involved in systemic inflammation. In fulminant liver failure, the serum level of TNF-α was significantly increased correlated with serious complications, such as infection and HE (de la Mata et al 1990;Zhao et al 2015). In the process of necroptosis, MLKL was phosphorylated and insert into the plasma membranes and organelles, which resulted in the expulsion of cellular contents into the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…A study has revealed that MMP-9 is closely related to CHB ( 17 ). TNF-α is the first inflammatory mediator produced in the body, which plays a core role in the occurrence and development of CHB and has crucial functions in the induction of inflammatory responses, anti-infection and host defense ( 18 ). IL-6 is a kind of lymphocyte factor of acute phase reaction with diversified effects, which accelerates the proliferation of myofibroblasts and leads to liver fibrosis in CHB patients ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] These represent a group of nuclear receptors that control cellular metabolism through the modulation of gene expression. [6] There are three distinct subtypes of PPARs: PPARα, PPARδ, and PPARγ. Activation of PPARγ has been shown to regulate glucose homeostasis, cellular differentiation, apoptosis, and inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%